2017
DOI: 10.1002/dev.21549
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal programming of postnatal plasticity for externalizing behavior: Testing an integrated developmental model of genetic and temperamental sensitivity to the environment

Abstract: Although both gene-environment and temperament-environment interactions contribute to the development of youth externalizing problems, it is unclear how these factors jointly affect environmental sensitivity over time. In a seven-year longitudinal study of 232 children (aged 5–10) with and without ADHD, we employed moderated mediation to test a developmentally-sensitive mechanistic model of genetic and temperamental sensitivity to prenatal and postnatal environmental factors. Birth weight, a global measure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…All of the included ADHD-related papers focused on candidate genes or candidate systems. For example, Tung and colleagues (2017) focused on SNPs within a number of dopaminergic genes [91]. A majority of the studies, however, included SNPs within the serotonin transporter gene as part of their gene-by-environment interaction [67, 68, 72-74, 76, 79-82, 84-86, 87•, 90, 92-95].…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…All of the included ADHD-related papers focused on candidate genes or candidate systems. For example, Tung and colleagues (2017) focused on SNPs within a number of dopaminergic genes [91]. A majority of the studies, however, included SNPs within the serotonin transporter gene as part of their gene-by-environment interaction [67, 68, 72-74, 76, 79-82, 84-86, 87•, 90, 92-95].…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…Parenting behaviors and postnatal psychological distress could also interact with prenatal distress to exacerbate or buffer risk for externalizing outcomes (Hartman et al, 2020; Tung et al, 2017). For example, one study reported that children exposed to both prenatal depression and childhood maltreatment had almost 12 times greater risk for developing psychopathology than children exposed to either risk factor alone (Pawlby et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the fifth of the proposed predictions, no interactive effect was found between negative emotionality and the parenting styles studied when explaining reactive and proactive aggressive behavior. Although it is true that negative emotionality has been related to a poor adjustment based on parenting [ 36 , 38 , 39 , 40 , 41 ], few studies have focused on aggressive behavior. Specifically, a study carried out by Pascual-Sagastizabal et al [ 42 ] found that high negative emotionality moderated the relationship between permissive paternal parenting and girls’ aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Negative emotionality has been found to interact with parenting to predict children’s emotion regulation [ 37 ]. When children with high levels of negative emotionality are exposed to a negative parenting style, they have poorer levels of adjustment, which are, in turn, positively associated with externalizing behavior [ 38 , 39 , 40 , 41 ]. Furthermore, in a recent study it was found that girls who had a high level of negative emotionality and were exposed to a permissive parenting style exercised by the father showed higher levels of aggressive behavior [ 42 ].…”
Section: Introductionmentioning
confidence: 99%